2020
DOI: 10.1021/acsaem.0c01097
|View full text |Cite
|
Sign up to set email alerts
|

Dithienogermole-Based Nonfullerene Acceptors: Roles of the Side-Chains’ Direction and Development of Green-Tinted Efficient Semitransparent Organic Solar Cells

Abstract: Inspired by the encouraging properties of Ge-fused heterocyclic dithienogermole (DTG) in optoelectronic applications, we here report two narrow-bandgap acceptor−donor′−donor− donor′−acceptor (A−D′−D−D′−A)-type isomeric nonfullerene acceptors based on DTG (DTG-IW with inward-facing side chains vs DTG-OW with outward-facing side chains) for use in organic solar cells (OSCs). The introduction of the inward-facing side chains into the backbone results in extremely confined face-on crystallites in the solid state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…The increased fluorine substituent in the end group lead BTP‐C9‐IC4F and BTP‐C9‐N4F exhibited highly ordered (11‐1) diffraction peaks in blend film. [ 59–61 ] In out‐of‐plane direction, the (010) peaks belonging to donor and acceptors highly overlapped. In the blend films, the introduction of acceptors significantly enhanced the π – π stacking.…”
Section: Resultsmentioning
confidence: 99%
“…The increased fluorine substituent in the end group lead BTP‐C9‐IC4F and BTP‐C9‐N4F exhibited highly ordered (11‐1) diffraction peaks in blend film. [ 59–61 ] In out‐of‐plane direction, the (010) peaks belonging to donor and acceptors highly overlapped. In the blend films, the introduction of acceptors significantly enhanced the π – π stacking.…”
Section: Resultsmentioning
confidence: 99%
“…Yang and co‐workers reported two new isomeric NBG‐NFAs based on a germanium (Ge)‐fused heterocyclic dithienogermole central donor and terminal 2F‐DCI units interconnected by a 2‐ethyl hexyl substituted thiophene unit with a different orientation of alkyl chains position, i.e., DTG‐IW (inward facing) and DTG‐IW (outward facing). [ 138 ] Though both of these NFAs had similar E g values of ≈1.3 eV, the GIWAXS study revealed that DTG‐IW contains highly confined “face‐on” crystallites in the solid state, which might be useful for boosting charge separation and transport in the corresponding devices. Optimized ST‐OSCs based on PTB7‐Th:DTG‐IW blends (green‐tinted color) and semitransparent Ag/Sb 2 O 3 /Ag electrodes delivered the best PCE of 6.19% and AT of 50.4% at 500–540 nm.…”
Section: Photoabsorbent Materials For St‐oscsmentioning
confidence: 99%
“…Grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) measurement is employed to evaluate the molecule stacking and crystallinity in solid thin films. [ 27 ] As shown in Figure a, the neat film of 4T‐1 had a (100) diffraction at q z = 0.33 Å −1 and a lattice fringe diffraction pattern, reflecting its higher crystallinity. The other three acceptors adopted an edge‐on molecular orientation with more intensive (010) and (100) diffractions along in‐plane (IP) and out‐of‐plane (OOP) directions, respectively.…”
Section: Resultsmentioning
confidence: 99%